Dari Keterlibatan Hidup Menuju Emansipasi Bersama: Sebuah Telaah Kritis Terhadap Konvivenz dalam Pemikiran Theo Sundermeier - Kritsno Saptenno (Program Pascasarjana UKIM, 2020)
Departed from his criticism of rigid mission practice and egocentric western philosophical hermeneutics, Sundermeier offers another point of view that mission should be oriented towards the process of interpretation and communication. Sundermeier came up with the idea of “hermeneutic of difference”, an intercultural hermeneutic approach that seeks to understand other cultures without appropriating them. Thereafter, Sundermeier arrived at konvivenz, a multicultural community that can share lives, have a good cultural understanding, and respect different aspects of each culture. According to Sundermeier, konvivenz can be a substructure for the relevant mission in the intercultural context. But, konvivenz seemed stuck on interpersonal relationships and overlooked the economic and political status gap that often makes equal intercultural relations impossible. Inter-cultural hermeneutic needs to consider the dimensions of emancipation in every cultural engagement.